Stimulating Foreign Language Teachers’ Professional Competence - qizi, Shukurova Marifat Xodjiakbar; Azimdjanovna, Nasiba Mulladjanova; Abdusattorovna, Laylo Yakhshiboeva; Muxammadovna, Nargiza Samandarova (The journal of contemporary issues in business and government, 2021)
The article provides an essential data about what is competence, competency and professional competences of foreign language teachers. It analyses how these terms are interconnected to one another and how they contrast. It defines variety of viewpoints of different scholars. The article presents the general and specific background about the target concepts and their contemporary worth. It is possible to identify how the theory is applied into practice in the sphere of foreign language teaching. The details are given step by step in order to clarify how the study is progressed. It creates the logical flow for the reader.